2010
DOI: 10.1016/j.talanta.2010.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Use of genetic algorithms with multivariate regression for determination of gelatine in historic papers based on FT-IR and NIR spectral data

Abstract: Quantitative non-destructive analysis of individual constituents of historic rag paper is crucial for its effective preservation. In this work, we examine the potentials of mid-and near-infrared spectroscopy, however, in order to fully utilise the selectivity inherent to spectroscopic multivariate measurements, genetic algorithms were used to select spectral data derived from information-rich FT-IR or UV-VIS-NIR measurements to build multivariate calibration models based on partial least squares regression, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The loss of accuracy is most probably related to the sampling variance. The quality of the model is similar to the quality of other dating models for chromogenic color prints (RMSECV = 5.4 years / 1942-2008 period) [32], and paper produced post-1850 (RMSEP = 9 years / 1850-1990 period) [31], and better than obtained for parchment (RMSECV = 72 years / 1200-1800 period) [35]. While the error of prediction (RMSEP) is acceptable, it is worth examining the uncertainty in the reference dates for the film stills.…”
Section: Development Of the Calibration Methodssupporting
confidence: 64%
See 4 more Smart Citations
“…The loss of accuracy is most probably related to the sampling variance. The quality of the model is similar to the quality of other dating models for chromogenic color prints (RMSECV = 5.4 years / 1942-2008 period) [32], and paper produced post-1850 (RMSEP = 9 years / 1850-1990 period) [31], and better than obtained for parchment (RMSECV = 72 years / 1200-1800 period) [35]. While the error of prediction (RMSEP) is acceptable, it is worth examining the uncertainty in the reference dates for the film stills.…”
Section: Development Of the Calibration Methodssupporting
confidence: 64%
“…The second component accounts for the variation in the scattering contribution (10000 -7000cm -1 region). The PC1 vs. PC2 scores plot (figure 5) evidences that the scattering is more pronounced for the thinner papers as expected if related to the presence of the baryta layer (previous studies have shown that effective path length in the case of paper is~0.5 mm [31], which is more than the thickest photographic paper in the sample set). The loadings plot for the third component confirms that some of the variation in the spectra is related to the presence of kaolin as already evidenced above.…”
Section: Exploratory Data Analysissupporting
confidence: 64%
See 3 more Smart Citations